THE EFFECT OF MOTIVATION AND WORK DISCIPLINE ON TEACHER PERFORMANCE WITH STUDENT LEARNING OUTCOMES AS INTERVENING VARIABLES FOR TEACHERS IN SUB RAYON 05 SELESAI - Suwito Suwito; Kiki Farida Ferine (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to analyze the effect of motivation and work discipline on teacher performance with student learning outcomes as intervening variables. This type of research is associative quantitative. The location was carried out at SMA Sub Rayon 05 Selesai. The population in this study was 81 teachers and the sample taken was a saturated sample. The data collection was carried out by distributing questionnaires. The research model used is Path Analysis and the measuring tool is Smart PLS 3.3.3. The results of his research are that Work Discipline has a positive and significant effect. Work Discipline has a positive and significant effect on teacher performance. Learning outcomes have no significant positive effect on teacher performance with the original sample value. Motivation has a positive and significant effect on learning outcomes. Motivation has a positive and insignificant effect on teacher performance. Work Discipline has a positive and insignificant effect on Teacher Performance through Learning Outcomes. Motivation has no significant positive effect on teacher performance through learning outcomes.